2022
DOI: 10.1002/jmv.28219
|View full text |Cite
|
Sign up to set email alerts
|

High titers of neutralizing antibodies in the blood fail to eliminate SARS‐CoV‐2 viral RNA in the upper respiratory tract

Abstract: Retest‐positive severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) viral RNA, as a unique phenomenon among discharged individuals, has been demonstrated to be safe in the community. Still, the underlying mechanism of viral lingering is less investigated. In this study, first, we find that the frequency of viral RNA‐positive retesting differs among variants. Higher ratios of viral RNA‐positive retest were more frequently observed among Delta (61.41%, 514 of 837 cases) and Omicron (39.53%, 119 of 301 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…All cases included in this study were local COVID-19 patients in Guangzhou as previously reported (Wang et al, 2021;Li et al, 2022;Li et al, 2023). The virus strains they were initially infected with were identified by whole viral genome sequencing.…”
Section: Identification Of Sars-cov-2 Strains In Initial Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…All cases included in this study were local COVID-19 patients in Guangzhou as previously reported (Wang et al, 2021;Li et al, 2022;Li et al, 2023). The virus strains they were initially infected with were identified by whole viral genome sequencing.…”
Section: Identification Of Sars-cov-2 Strains In Initial Infectionmentioning
confidence: 99%
“…During the COVID-19 pandemic period, patients infected with various virus strains in Guangzhou were admitted to the Guangzhou Eighth People's Hospital, Guangzhou Medical University, China. The ancestral strain was first reported on January 20, 2020, and the Delta and Omicron BA.2 variants primarily emerged on May 21, 2021 and April 8, 2022, respectively (Wang et al, 2020;Wang et al, 2021;Li et al, 2023). Some of these cases reinfected with the Omicron BA.5 variant between December, 2022 and January, 2023 according to the telephone questionnaires (Figure 1A).…”
Section: Demographic and Clinical Characteristics Of Subjects During ...mentioning
confidence: 99%